2021
DOI: 10.3389/fsurg.2021.682930
|View full text |Cite
|
Sign up to set email alerts
|

Age at Diagnosis and Baseline Myelomalacia Sign Predict Functional Outcome After Spinal Meningioma Surgery

Abstract: Objective: Spinal meningioma (SM) accounts for 12% of all meningiomas. Clinical and immunohistochemical factors were analyzed with regard to functional outcome, surgical adverse events, and tumor recurrence.Methods: One-hundred and twenty-three consecutive SM patients underwent surgery and were retrospectively reviewed with regard to demographic parameters, imaging features, neurological function, and immunohistochemical items. Neurological function was graded according to the Modified McCormick Scale (MMS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
(72 reference statements)
2
5
2
Order By: Relevance
“…Furthermore, patients in the cohort with severe symptoms were older, had more frequent tumors in the thoracic spine, with higher spinal canal occupancy ratio and spinal cord edema. The impact of the spinal canal ratio on neurological deficits was also demonstrated in previously published studies [2,20,[23][24][25][26]. These all seem to be risk factors for developing more severe deficits or a delay in diagnostics [20].…”
Section: Neurological Outcome After Minimal-invasive Resectionsupporting
confidence: 63%
“…Furthermore, patients in the cohort with severe symptoms were older, had more frequent tumors in the thoracic spine, with higher spinal canal occupancy ratio and spinal cord edema. The impact of the spinal canal ratio on neurological deficits was also demonstrated in previously published studies [2,20,[23][24][25][26]. These all seem to be risk factors for developing more severe deficits or a delay in diagnostics [20].…”
Section: Neurological Outcome After Minimal-invasive Resectionsupporting
confidence: 63%
“…Patients with ventral spinal meningiomas may hence carry a higher risk of complications [ 41 ]. One study found significant ties between CSF fistula formation and ventral tumor location, with an odds ratio (OR) estimated at 10.5 [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other factors significantly associated with an increased risk of perioperative complications were obesity [ 47 , 48 ] (OR: 3.2 in one study [ 49 ]), surgery for recurrent tumors [ 48 , 49 , 50 ], surgeon inexperience [ 48 ], and tumor calcification [ 30 ]. Additionally, longer operations were associated with an increased risk of postoperative CSF leak [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical data including age, sex, neurological functioning, presence of symptomatic epilepsy, Modified McCormick (MMS) scale in spinal meningiomas, comorbidities, Karnofsky Performance Status (KPS), body mass index (BMI), anatomic location, WHO grading based on postoperative neuropathological investigation, immunohistochemical analysis, extent of meningioma resection based on Simpson grading system according to the European Association of Neuro-Oncology (EANO) (Simpson grade I–III = gross total resection, Simpson grade IV = subtotal resection, and Simpson grade V = biopsy), and postoperative follow-up data were saved into a computerized database (SPSS, version 27 for Windows, IBM Crop., Armonk, NY, USA) [ 16 , 25 ]. Modified McCormick scale was dichotomized into “good” (I + II) and “poor” (III–V) as described previously [ 26 ]. Anatomical location was dichotomized into cranial and spinal meningioma.…”
Section: Methodsmentioning
confidence: 99%